Evaluating Noise Reduction Methods for Raman Spectroscopy in Transmission and Reflection Configurations - Wasunun Sassuvun; Prathan Buranasiri; Surawut Wicharn; Chokchai Puttharugsa; Puenisara Limnonthakul; Saksorn Limwichean; Suwan Plaipichit (My University, 2024)
This work involved comparing Raman signals obtained from two different Raman spectroscopy configurations, using two distinct noise reduction methods. The excitation light source was a laser diode with a wavelength of 532 nm. A long-pass filter and focusing lens were utilized to block the excited light from the source and concentrate the Raman signals due to their weaker nature compared to the excited light signals. Light of 532 nm wavelength was blocked during green laser diode illumination using a long-pass filter. Two configurations were studied: transmission Raman spectroscopy (TRS) and reflection Raman spectroscopy (RRS). Raman signals from both configurations were compared, and the boxcar averaging and Vancouver Raman algorithm (VRA) noise reduction methods were investigated and compared. The results showed that Raman signals from the transmission configuration were higher than those from the reflection configuration, and noise signals were effectively reduced using both the boxcar averaging and VRA methods.
Keywords: Reflection; Spectroscopy Techniques in Biomedical and Chemical Research